The effect of gallic acid on memory and anxiety-like behaviors in rats with bile duct ligation-induced hepatic encephalopathy: Role of AMPK pathway - Ieila Jafaripour; Khadijeh Esmaeilpour; Marzieh Maneshian; Hamideh Bashiri; Mohammad Amin Rajizadeh; Hassan Ahmadvand; Majid Asadi-Shekaari (Mashhad University of Medical Sciences, 2022)
Objective: Hepatic encephalopathy (HE) is a serious neurological syndrome which is caused by acute and chronic liver diseases. In this study, the effect of gallic acid (GA) as an activator of AMP-activated protein kinase (AMPK) on memory and anxiety-like behaviors in rats with HE caused by bile duct ligation (BDL) was investigated.Materials and Methods: The rats were randomly divided into the following eight groups (n=7): sham; BDL; BDL+GA 20 mg/kg; BDL+GA 30 mg/kg; sham+dorsomorphin or compound C (CC) (as AMPK inhibitors); BDL+CC; BDL+GA 20 mg/kg+CC; and BDL+GA 30 mg/kg+CC. The rats received GA once daily by gavage for four weeks, and dorsomorphin 6.2 µg per rat was administered on a daily basis via bilateral intraventricular injection for four weeks. Behavioral tests including novel object recognition (NOR), open field and Morris water maze (MWM) were used to evaluate anxiety and memory in the rats.Results: Examining some parameters of NOR and MWM tests showed that memory performance was significantly reduced in the BDL versus the sham group, and in the BDL+CC versus the sham+CC group (p<0.05). GA intake improved memory in the GA-receiving groups compared with the BDL and BDL+CC groups (p<0.05). Examining some parameters of open field test showed that anxiety was significantly increased in the BDL versus the sham group, and the BDL+CC versus the sham+CC group (p<0.05). GA intake reduced anxiety in GA-receiving groups compared with the BDL+BDL+CC group (p<0.05).Conclusion: GA was effective in improving cognitive and anxiety-like behaviors through activating AMPK.